Methodology of physical activities for obese older adults with sedentary habits - Diego Samper Rivero; Jorge de Lázaro Coll Costa; Douglas Crispín Castellanos (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
Currently the number of obese people increases considerably, becoming a concern because of the health problems caused by this disease. Although physical activity is considered beneficial, in overweight people it can have some negative effects. This research was carried out in the 34th circumscription of the Consejo Popular Centro Histórico, of Nueva Gerona in the Isla de la Juventud, Cuba with the objective of proposing a methodology of physical activities for obese older adults with sedentary habits of 65 years of age and older from this community taking advantage of the marine aquatic environment. For this purpose, a mixed methodology was used, based on descriptive methods: analytical-synthetic and abstract logic, as well as through experimental analysis such as: scientific observation, surveys, interviews; statistic methods were also used to process the information obtained, mode and median. As a result of this methodology, the lifestyle was improved and contributed to the reduction of fat in obese older adults in this community taking advantage of the marine aquatic environment.